(2,2′-Bipyridyl-κ(2) N,N′)bis(N-butyl-N-methyldithiocarbamato-κ(2) S,S′)cadmium(II) - Jamaluddin, Nur Amirah (International Union of Crystallography, 2011)
The Cd(II) atom in the title compound, [Cd(C(6)H(12)NS(2))(2)(C(10)H(8)N(2))], is hexacoordinated by two dithiocarbamate ligands and the N atoms from a bidentate 2,2′-bipyridyl molecule. The coordination geometry is based on a distorted trigonal–prismatic arrangement of the N(2)S(4) donor set. Supramolecular chains, aligned along the a-axis direction, are mediated by C—H⋯S interactions and these are connected into layers that stack along the c axis via π–π interactions [Cg(pyridyl)⋯Cg(pyridyl) = 3.6587 (13) Å].